Evaluation of miR-122 and Other Biomarkers in Distinct Acute Liver Injury in Rats. (July 2013) - Starckx, Sofie; Batheja, Ameesha; Verheyen, Geert R.; Jonghe, Sandra De; Steemans, Kristel; Dijck, Bram Van; Singer, Monica; Bogdan, Nancy; Snoeys, Jan; Vinken, Petra; Sasaki, Jennifer C.; Gompel, Jacky Van; et al.
The detection of drug-induced hepatotoxicity remains an important safety issue in drug development. A liver-specific microRNA species, microRNA-122 (miR-122), has recently shown potential for predicting liver injury in addition to the standard hepatic injury biomarkers. The objective of this study was to measure miR-122 together with several other liver markers in distinct settings of acute liver toxicity in rats to determine the value of miR-122 as a biomarker for liver injury in this species. Rats were exposed to 3 well-established liver toxicants (acetaminophen, allyl alcohol, and α-naphthyl isothiocyanate), a liver-enzyme inducer (phenobarbital), or a cardiotoxicant (doxorubicin). There was a clear increase in plasma miR-122 following administration of acetaminophen, allyl alcohol, and α-naphthyl isothiocyanate. The response of miR-122 paralleled that of other markers and was consistent with liver injury as indicated by histopathological evaluation. Furthermore, the changes in miR-122 were detected earlier than standard liver injury markers and exhibited a wide dynamic range. In contrast, miR-122 responses to phenobarbital and doxorubicin were low. Based on these findings, miR-122 shows significant promise and may provide added value for assessing liver toxicity in drug development.